Shelf-life extension of fresh-cut mango by coating with cactus extract - Tatsaporn Todhanakasem; Phuttipong Eamsiriluck; Ronakit Nimitr; Rachit Suwapanich; Kamolnate Kitsawad Maleenont (Applied Food Research, 2025)
• Formulated cactus coating could improve the shelf life of the fresh-cut mango by maintaining the physicochemical properties and hindering microbial growth • Adding up the phenolic content and other active compounds to promote health benefits • No effect on overall consumer preferences Edible coating of fresh-cut fruit with functional ingredients has been adopted recently as a practical technology for enhancing safety, nutritional, freshness, and sensory attributes. This research aims to spray-coat fresh-cut mango with extracts from two types of cactus ( Opuntia dillenii and Opuntia ficus-indica ) in combination with gelatin, glycerol, and fructooligosaccharide. The O. ficus-indica coating tended to provide significant improvements, with two times less weight loss than the control. Physicochemical assay results (total soluble solids, pH, percent citric acid, total phenolic content and firmness) also showed to maintain the quality of fresh-cut mango and hinder growth of microorganisms (10 4 CFU/ml with the coating versus 10 5 CFU/mL without) in fruit refrigerated at 4°C for ten days. Meanwhile, coating with O. dillenii extract significantly increased of phenolic content on day 10 of storage (785.94 µg GAE/g sample), which has potential health benefit as well as helping to extend the product’s shelf life. In addition, it represented the highest potential in inhibiting the total color change during refrigerated storage. Both coatings had no effect on overall consumer liking when the sensory analysis was performed. Therefore, Opuntia cactus extracts have promise as components of a bioactive edible coating to improve the shelf life of fresh-cut mango and promote health benefits to consumers.
Keywords: Botanical Research and Applications; Postharvest Quality and Shelf Life Management; Nanocomposite Films for Food Packaging